2016
DOI: 10.15537/smj.2016.12.16163
|View full text |Cite
|
Sign up to set email alerts
|

Phase down of amalgam

Abstract: ObjectivesTo assess the knowledge of Jordanian dentists toward phase down of dental amalgam as recommended by the Minamata Convention, and their training and competency in placing posterior composites.MethodsThis study was conducted through structured questionnaire interviews with randomly selected cohort of dentists in Jordan between March 2015 and June 2015. Out of 230 dentists who were invited, 196 (85.2%) agreed to participate. Dentists were asked if they know about the Minamata Convention. They were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 28 publications
(41 reference statements)
1
15
0
Order By: Relevance
“…carried out a study among Jordanian dentists and reported that few dentists (13.8%) had knowledge of the Minamata Convention, and only 17% of the study population had undergraduate orientation in support of restoring posterior teeth with composite. They also revealed that only 28.1% of these practicing dentists were convinced that amalgam should be discontinued in consideration of the reported health and environmental safety concerns. The senior resident doctors in the present study were more likely than the younger clinicians to place resin composite and GIC restorations, this may be as a result of this senior group of dentists being more confident in the use of these adhesive materials, which are more technique sensitive in comparison to the placement of amalgam restorations.…”
Section: Discussionmentioning
confidence: 58%
“…carried out a study among Jordanian dentists and reported that few dentists (13.8%) had knowledge of the Minamata Convention, and only 17% of the study population had undergraduate orientation in support of restoring posterior teeth with composite. They also revealed that only 28.1% of these practicing dentists were convinced that amalgam should be discontinued in consideration of the reported health and environmental safety concerns. The senior resident doctors in the present study were more likely than the younger clinicians to place resin composite and GIC restorations, this may be as a result of this senior group of dentists being more confident in the use of these adhesive materials, which are more technique sensitive in comparison to the placement of amalgam restorations.…”
Section: Discussionmentioning
confidence: 58%
“…Al-Rabab'ah et al 11 reported an even lower percentage of Jordanian dentists (17%) who had received undergraduate training in placement of posterior resin composite. 11 Dentists who completed their undergraduate studies before the implementation of the Minamata Convention would have received training in restorative dentistry focused on amalgam, and these professionals are most likely to resist the shift from amalgam to other restorative dental materials. Our findings highlight the need to conduct continuing dental education in adhesive/operative dentistry at several easily accessible centres across the country to impart this knowledge to dentists lacking operative dental skills in the area of adhesive dentistry.…”
Section: Discussionmentioning
confidence: 99%
“…Over 50% (52.4%) were unaware, 13.2% were unconvinced, and 39.2% were uncertain regarding the health hazards associated with the mercury content of amalgam specified by the UNEP and other international bodies. Al-Rabab'ah et al 11 also reported that only 28.1% of Jordanian dentists were convinced that amalgam use needs to be discontinued owing to the alleged health and environmental hazards associated with its use. 11 Of the 741 participants with poor knowledge of the Minamata Convention, 31 (4.2%) admitted to adopting good phase-down practices, which could be attributed to the increasing demand for tooth-coloured restorative materials by patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations